2019
DOI: 10.1371/journal.pone.0213723
|View full text |Cite
|
Sign up to set email alerts
|

Cost and cost-effectiveness of health behavior change interventions implemented with self-help groups in Bihar, India

Abstract: Introduction Health interventions implemented with self-help groups (SHGs) enhance the relevance and acceptability of the health services. The Parivartan program was implemented in eight districts of Bihar with women’s self-help groups to increase adoption of maternal and newborn health behaviors through layering health behavior change communication. This study estimates the cost and cost-effectiveness of a health behavior change program with SHGs in Bihar. Methods Cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 11 publications
5
21
0
Order By: Relevance
“…Both components synergistically operating may also help to interrupt the mutually reinforcing cycle of poverty and poor maternal health. Evidence from a study in the state of Bihar, India also established the cost-effectiveness in promoting maternal and neonatal health when microfinance and health interventions are implemented at scale [53]. However, further research is required to capture costs effectiveness in promoting integrated microfinance and health interventions in Uttar Pradesh that is culturally distinct.…”
Section: Resultsmentioning
confidence: 99%
“…Both components synergistically operating may also help to interrupt the mutually reinforcing cycle of poverty and poor maternal health. Evidence from a study in the state of Bihar, India also established the cost-effectiveness in promoting maternal and neonatal health when microfinance and health interventions are implemented at scale [53]. However, further research is required to capture costs effectiveness in promoting integrated microfinance and health interventions in Uttar Pradesh that is culturally distinct.…”
Section: Resultsmentioning
confidence: 99%
“…The SHG model used in the IMFHL program additionally allows for rapidly scaling up, and the dissemination of developmental services to a largely marginalised and hard to reach population. Furthermore, micro nance and health interventions have also been found to be cost-effective in promoting maternal and neonatal health from another study conducted in the state of Bihar, India which has similar health and developmental indicators to Uttar Pradesh (72). Despite gains in knowledge of maternal danger signs, further research is required to establish the impact of membership in IMFHL programs on actual care-seeking practices among women who have experienced complications in the maternity period.…”
Section: Resultsmentioning
confidence: 99%
“…The SHG model used in the IMFHL program additionally allows for rapidly scaling up, and the dissemination of developmental services to a largely marginalised and hard to reach population. Furthermore, an earlier study found microfinance and health interventions to be cost-effective in promoting maternal and neonatal health in Bihar, India which has similar health and developmental indicators to Uttar Pradesh [ 77 ]. Despite gains in knowledge of maternal danger signs, further research is required to establish the impact of membership in IMFHL programs on actual care-seeking practices among women who have experienced complications in the maternity period.…”
Section: Discussionmentioning
confidence: 99%